Comparative Evaluation of the Effectiveness of Manual and Electric Toothbrushes in Blind Children: A Randomised Controlled Trial - PS Thanalakshme; R Ramesh (Journal of Clinical and Diagnostic Research)
Introduction: Plaque removal is vital for preventing gingivitis and periodontitis, while maintaining oral hygiene is crucial for overall health. Blind children face unique challenges in oral care due to their reliance on touch rather than visual cues, which makes proper brushing difficult. Although research is limited, electric toothbrushes have been proposed as a solution to help blind children remove plaque more effectively by compensating for their reduced ability to visually monitor their brushing technique. Further studies are needed to confirm their benefits. Aim: To evaluate the effectiveness of manual and electric toothbrushes in promoting better oral hygiene in visually impaired children in Palayamkottai, Tirunelveli District. Materials and Methods: A randomised controlled clinical trial conducted at a high school for the blind in Palayamkottai, Tirunelveli district, Tamil Nadu, India on 120 blind chidren aged 6-12 years. The study participants was divided into Group 1, the manual toothbrush group, received a standard soft-bristle manual toothbrush (Colgate Sanxiao Co., Ltd., No. 8 Gaolujie Road, Guang Ling District, Yangzhou, 225111). In Group 2, the electric toothbrush group, participants were provided with a MINISO electric toothbrush with soft silicone bristles. Key parameters- Plaque Index (PI), Patient Hygiene Performance (PHP) index, Decayed, Missing, and Filled Teeth (DMFT) index, and Ayesha’s Oddbods Dental Anxiety Scale (AODAS) were measured at baseline, three months, and six months. Descriptive statistics were used to summarise demographic and clinical data. Repeated measures Analysis of Variance (ANOVA) were used to analyse the changes in the PI, PHP Index, and DMFT indices, as well as anxiety levels over time. A paired t-test was used to compare oral health outcomes and anxiety levels between the two groups. Results: Over the course of six months, the study showed that manual toothbrushes were superior to electronic toothbrushes in enhancing oral health in blind children. The PI (2.4±5.04 to 0.39±0.49), PHP Index (2.24±0.65 to 0.45±0.50), and DMFT Index (2.45±0.50 to 0.53±0.54) all significantly decreased in Group 1 (manual), while Group 2 (electric) exhibited less noticeable changes. Furthermore, compared to Group 2 (32.7±5.3 to 11.7±3.7), dental anxiety decreased more in Group 1 (32.8±5.3 to 7.9±3.2). Conclusion: In present study, manual toothbrushes outperformed electronic toothbrushes in enhancing oral health in blind children. Better gingival health and plaque clearance may have been facilitated by the tactile input of manual brushing. For blind children to maintain good oral health, it is advised to follow consistent oral hygiene practices and customise therapies.